HUBUNGAN KECERDASAN EMOSIONAL DENGAN HASIL BELAJAR PADA MATA PELAJARAN SENI BUDAYA BIDANG SENI RUPA KELAS VII SMP NEGERI 9 PADANG - FAISAL, Dra. Zubaidah, M.Pd. (Universitas Negeri Padang, 2019)
In accordance with the problem of this research the aim is to describe the relationship between emotional intelligence and learning outcomes in cultural arts subjects in the seventh grade of Padang State Junior High School 9. This type of research includes correlational quantitative research. While the population in this study were all class VII of Padang State Middle School, namely the total number of 225 students with Proportional Random Sampling sampling techniques. This collection of emotional intelligence variables in the form of questionnaires with 60 statement items. the statement item to 72 students as a sample. While the results of the study variables ar data obtained from students' daily exams (UH). Based on the processing and results of the study, then r count = 0.527 and rtable0.235. At á = 0.05. Percentage of test results with a hypothesis of 27.77%. Based on the results obtained, it can be concluded that the hypothesis in this study is acceptable because of the relationship between emotional intelligence and student learning outcomesKeywords : Emotional Intellegence (EQ).Learning Outcomes